THE EFFECT OF EMPLOYEE STATUS ON EMPLOYEE SATISFACTION WITH INCENTIVES AS AN INTERVENING VARIABLE (Case Study on Employees of Russian Medical Doctor and Nurses) - Arnaud Costinot; Alexander (PT. Radja Intercontinental Publishing, 2022)
In this study, the population was employees of Russian Medical Doctor and Nurses, namely as many as 30 people. Because the target population is less than 100, the sampling technique used is the census method, in which the entire population, totaling 30 employees of Russian Medical Doctor and Nurses. Made the sample in this study. Data analysis is a desire to classify, make a sequence, manipulate and abbreviate data so that it is easy to read and understand. In other words, data analysis activities are raw data that has been collected needs to be categorized or divided into several categories or groups, shortened in such a way that the data can answer problems according to research objectives and can test hypotheses. With the results of the first hypothesis accepted, meaning that the variable Working Status (X) has a positive and significant effect on incentives (Y1). the second hypothesis is accepted, meaning that Work Status (X) has a significant effect on Job Satisfaction (Y2). the third hypothesis is accepted, meaning that incentives (Y1) have a positive and significant effect on job satisfaction (Y2). The calculation results obtained show that the indirect effect through the Y1 variable is greater than the direct effect on the Y2 variable.